Al majdal - BADIL Resource Center for Palestinian Residency and Refugee Rights (Bethlehem BADIL Resource Center, 2007)
al-Majdal is BADIL's magazine on Palestinian refugees. The magazine aims to raise public awareness and support for a just solution to Palestinian residency and refugee issues.
Issue 36/37 special Nakba 60
Keywords: Political refugees; POLITICAL REFUGEES; PALESTINE REFUGEES; REPATRIATION; ARAB-ISRAELI CONFLICT; PERIODICALS